Training Interventions for Improved Deceleration Ability in Adult Team-Based Field Sports Athletes - Louise Marvin; Paul Read; Blake McLean; Sam Palmer; Job Fransen (International Universities Strength and Conditioning Association, 2024)
Background: Deceleration is a fundamental component of multidirectional speed by which athletes reduce the velocity of their centre of mass to stop or execute changes of direction following acceleration or running at a constant velocity. Enhancing deceleration abilities is crucial for athletes as successfully executing horizontal deceleration has important implications for match outcomes in sports requiring rapid multidirectional movements. However, specific training interventions targeting deceleration are scarce. The purpose of this systematic review and meta-analysis was to examine the effects of training interventions on deceleration performance in adult team-based field and court sports athletes. Methods: A systematic literature search was conducted through electronic databases, SPORTdiscus, PubMed, and Web of Science from inception to February 2022, and re-run in May 2023. The search terms were related to different training interventions and kinetic, kinematic, and performance outcomes related to deceleration performance. Studies were included if they consisted of a randomised controlled trial which investigated the effects of training on deceleration-specific outcome measures in adult team-based field and court sports athletes. Risk of bias was assessed using the revised Cochrane risk-of-bias tool for randomised trials (RoB2). Post-intervention effect sizes (Hedge's g) were calculated between the intervention and control groups and a meta-analysis was performed using a random effects model. Results: Twelve studies were included, with 29 deceleration-specific outcomes measured in a total of 381 participants. There was inconsistency in methodological designs, including control group types, length and type of interventions and in reported deceleration-specific outcome measures. Across all observations of deceleration performance measures there was a standardised mean difference of -0.04 (95% CI: -0.50, 0.42), favouring control groups, indicating little effect of training on deceleration performance. For secondary outcomes related to deceleration, for kinetics (SMD = -0.29, 95% CI = -0.83, 0.25, I2 = 55%, p < 0.01), joint kinetics (SMD = -0.20, 95% CI = -1.01, 0.61, I2 = 68%, p < 0.01) and muscle activation (SMD = -0.10, 95% CI = -0.44, 0.24, I2 = 19%, p = 0.28) had greater effects for control groups, whereas joint kinematics (SMD = 0.07, 95% CI = -0.11, 0.24, I2 = 0%, p = 0.77), favoured the intervention groups. Conclusion: For the deceleration-specific outcomes reported in the included studies, training was not likely to produce a performance improvement in participants compared to control groups. However, due to methodological inconsistencies between studies and observed high risk of bias, the results should be interpreted with caution. More rigorous research methods should be included in the future to address areas that may introduce potential biases. Future research should address the differences in the type, timing, frequency, and duration of the implemented training interventions for improving deceleration performance, and in the reported deceleration-specific outcome measures. Registration: This systematic review was registered on the Open Science Framework (https://osf.io/cmwbr) (https://doi.org/10.17605/OSF.IO/CMWBR)